Pacific Coast Feather : winds of change - Swab, R. Gabrielle, (SAGE Knowledge. Cases., 2018)
Pacific Coast Feather focuses on manufacturing and selling pillows, comforters, and mattress pads. The company and its major competitors do most of their production within the United States, using imported materials. With large orders on the horizon and plans for company growth, a tornado leveled their mattress pad plant, wiping out the ability to produce this key product line and fulfill the current orders. The company president was left to evaluate alternatives for this business. The case study takes a close look into this industry, as well as the decisions the company president was faced with in evaluating the next step for their product.